Exploring Ways to Investigate Instructors’ Roles in Facilitating Transformative Learning Processes for International Students - Lee W. Nabb; Kristi Archuleta Frush (Adult Education Research Conference, 2010)
The purpose of this roundtable session is to identify, and develop ideas and methods to research ways in which face-to-face and online instructors of international students can most effectively facilitate positive transformation. The transitions and challenges that international students often experience will be discussed as well as varying perspectives about how these adult learners can be optimally supported. The benefits and limitations of previous research methods used to investigate international students’ transformation will be explored.